IN VITRO ACTIVITY OF ENROFLOXACIN AGAINST CLINICAL ESCHERICHIA COLI AND NON-LACTOSE FERMENTING ENTEROBACTERIA ISOLATES FROM CHICKENS IN BENUE STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
Clinical bacterial isolates from chickens were analysed to determine their susceptibilities to antimicrobial agent. Ten (10) Escherichia coli and 8 non lactose fermenting Enterobacteriaceae species isolated from a pool of clinical cases of chickens from Microbiology Laboratory of the Veterinary Teaching Hospital, University of Agriculture Makurdi were used for the study. Enrofloxacin with 99 % purity obtained from Sigma-Aldriech, USA and prepared in varying concentrations (0.1 - 50μg/mL) was used in vitro by Kirby-Bauer’s disc-diffusion method. The isolates were susceptible to enrofloxacin at a minimum concentration of 25 (μg/mL) and the mean value in the zones of inhibition exhibited by Escherichia coli and non-lactose fermenters were significantly different (p
Keywords: Antibacterial, Chicken, Enrofloxacin, Escherichia coli, Non-lactose fermenter